Caribbean region. Annual report 2007 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
Contents: 1. Implementation of the regional technical cooperation agenda in 2007. 2 Results of Inter-Agency Cooperation. 3 Country executive summaries. 4 New opportunities for technical cooperation.